2015
DOI: 10.1002/mc.22389
|View full text |Cite
|
Sign up to set email alerts
|

S100A4 hypomethylation affects epithelial-mesenchymal transition partially induced by LMP2A in nasopharyngeal carcinoma

Abstract: To identify cellular target genes involved in NPC cell invasion and metastasis, gene expression profiles of CNE-1 cells with or without ectopic LMP2A expression were compared by using the metastatic gene array. S100 calcium binding protein A4 (S100A4) was the highest increased one among these genes both in mRNA and protein levels of NPC cells. Moreover, S100A4 was upregulated in LMP2A-positive NPC tissues. We found that CNE-1-S100A4 showed significantly increased invasion ability as compared to the controls bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Moreover, we verified this phenomenon in lung adenocarcinoma cell lines with high versus low metastasis properties. In line with our findings, DNA hypomethylation and enhanced gene expression of S100A4 can increase invasive ability and promote metastasis in nasopharyngeal, laryngeal, and endometrial carcinoma [ 12 , 15 , 16 ]. Likewise, increased S100A6 expression and its DNA hypomethylation are associated with poor prognosis in gastric cancer [ 13 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, we verified this phenomenon in lung adenocarcinoma cell lines with high versus low metastasis properties. In line with our findings, DNA hypomethylation and enhanced gene expression of S100A4 can increase invasive ability and promote metastasis in nasopharyngeal, laryngeal, and endometrial carcinoma [ 12 , 15 , 16 ]. Likewise, increased S100A6 expression and its DNA hypomethylation are associated with poor prognosis in gastric cancer [ 13 ].…”
Section: Discussionsupporting
confidence: 88%
“…Recently, several S100A family members have been recognized as a critical regulator of the metastatic process and epithelial-mesenchymal transition occurrence in several human cancers. Among them, S100A4 and S100A6 have been reported to be epigenetically up-regulated in nasopharyngeal and gastric cancer by DNA hypomethylation over their gene promoter regions, while S100A2 and S100A10 down-regulated in head/neck and pituitary cancer by DNA hypermethylation [ 12 , 13 ]. Our data provide evidence that S100A15 aggravates metastatic progressing in lung adenocarcinoma in vivo and in vitro through DNA hypomethylation over its gene promoter region, and CTNNB1-centered down-stream mediators.…”
Section: Discussionmentioning
confidence: 99%
“…With this line of evidence, we intrasplenically injected HCT116 cells stably overexpressing miR-520c-3p in SCID beige mice and observed slightly reduced metastasis formation in the liver compared to the control-miR group. With this results, one can speculate that especially in this context the downregulation of miR-520c-3p due to a hypermethylation of its regulatory region could be one of the mechanisms for S100A4 overexpression in different cancer entities, apart from its previously described epigenetic and Wnt/β-catenin mediated transcriptional regulation [14, 58]. …”
Section: Discussionmentioning
confidence: 89%
“…For example, S100 calcium binding protein A4 (S100A4) induces EMT and promotes metastasis and was reported to be hypomethylated and upregulated in LMP2A-positive NPC tissues. 76 Another study reported that the synergistic hypomethylation of Jagged1 and Notch1 genes was involved in the metastasis of breast cancer. 77 In addition, Iroquois homeobox 1 (IRX1) hypomethylation is a potential molecular marker for lung metastasis.…”
Section: Dna Methylation Dysregulation In Cancer Metastasismentioning
confidence: 99%